PENINGKATAN KOMPETENSI PETANI PADI SAWAH MELALUI PERANAN PENYULUH PERTANIAN DI KECAMATAN TOJO KABUPATEN TOJO UNA - UNA - Kusumaningrum, Widyawati; Pangli, Marten; Tanari, Yulinda (JURNAL BIOINDUSTRI (JOURNAL OF BIOINDUSTRY), 2023)
Agricultural extension agents have a role as a motivator, dynamist, facilitator and communicator. Therefore, extension workers have an important role to provide knowledge to farmers about improving farming and crop productivity, in this case rice farming in Tojo District, Tojo Una-Una Regency. This research was carried out from May to August 2020 in Tojo District, Tojo Una-Una Regency and the objective was to determine the role of agricultural extension workers in increasing the competence of paddy field farmers. The research was carried out using quantitative methods with a total sample of 144 paddy field farmers. Based on the research results, the role of extension workers as advisors increases the competence of paddy field farmers in the cultivation aspect, while the role of extension agents as motivators, dynamists, communicators and facilitators was very significantly negatively related to the competence of farmers in aspects of cultivation and harvesting.